Living with multimorbidity: medical and lay healthcare approaches. (April 2015) - Porter, Tom; Sanders, Tom; Richardson, Jane; Grime, Janet; Ong, Bie Nio
Multimorbidity is rapidly becoming the norm rather than the exception in healthcare. Research on this issue is increasing and this review discusses a selection of clinical and social science literature. The focus is on understanding the complexity of the lived experience of multimorbidity and how this is presented in clinical encounters, drawing on examples of arthritis within a multimorbidity context. Taking into account the biophysical, psychological, social and cultural factors that shape multimorbidity this paper calls for a re-conceptualization of the concept, allowing a more dynamic and holistic approach.